Computational Analysis of Renewable Fuel Synthesis in Intensified Reactors - Hafeez, Sanaa (London South Bank University, 2021)
The objective of this thesis is to theoretically investigate the production of renewable fuels in microreactors, in order to understand and optimise the process. The constant strain on fossil fuels, and the serious global issues associated with their use, has led to the production of renewable fuels. Theoretical methodologies, such as Computational Fluid Dynamics (CFD) and process simulation modelling, were employed to study various renewable fuel production reactions. Biofuels are an attractive alternative to conventional fossil fuels to be used for transportation purposes. Initially, the hydrodeoxygenation of bio-oil was studied in a packed bed microreactor using experimental results from literature. A pseudo homogeneous model was developed to establish the reaction process parameters, and to obtain a good validation with the experimental results. Subsequently, the theoretical model was upgraded to a multiphase heterogeneous model which incorporated the particle fluid transport phenomena to perform detailed parametric studies, such as rate analysis and internal and external mass transfer resistances. The CFD modelling techniques established were used to study the selective catalytic deoxygenation of palm oil. The comprehensive model was implemented to study the deactivation of the solid catalysts, and further parametric studies were conducted to determine the optimisation parameters.